Design of precision variable-rate spray system for unmanned aerial vehicle using automatic control method - Lian, Qi; Tan, Feng; Fu, Xiaoming; Zhang, Ping; Liu, Xin; Zhang, Wei (International Journal of Agricultural and Biological Engineering, 2019)
In order to reduce the use of chemical pesticides in crop plant protection and improve the utilization efficiency of pesticides, it is necessary to study advanced application machinery and application techniques. The use of unmanned aerial vehicle (UAV) for pesticide spraying has the characteristics of less application, strong penetrability, wide applicability and flexible operation scheduling, and has gradually become one of the important development directions in the field of aviation plant protection. However, the operation process of the UAV is often affected by meteorological factors and human manipulation, resulting in poor actual operation with inaccurate spray volume and uneven application. Therefore, to improve the stability and uniformity of the application of the plant protection UAV under variable operating conditions, in this paper a real-time control method was proposed for the application flow rate, and a precision variable-rate spray system was designed based on single-chip microcomputer and micro diaphragm pump that can controls the flow rate of the pump in real time with the changes of the operating state. The response s-peed of the variable-rate spray system was tested. The average control response time of the system was 0.18 s, and the average stability time of the pump flow change was 0.75 s. The test results showed that the system has a quick response to the working state and the adjustment of the target flow of the pump can be quickly completed to realize the variable-rate spray function. The research results can provide a reference for the practical application of plant protection UAV variable-rate spray system. Keywords: UAV, plant protection, automatic control, spray system, variable-rate spray, precision application DOI: 10.25165/j.ijabe.20191202.4701 Citation: Lian Q, Tan F, Fu X M, Liu X, Zhang P, Zhang W. Design of precision variable-rate spray system for unmanned aerial vehicle using automatic control method. Int J Agric & Biol Eng, 2019; 12(2): 29–35.